Inflation-type compound-channel evaporator for solar direct-expansion heat pump water heater - WU JINGYI; CHEN JINFENG; DAI YANJUN; SUN XIAOLIN; WANG RUZHU; SUN PENG (2013)
The invention discloses an inflation-type compound-channel evaporator for a solar direct-expansion heat pump water heater. The inflation-type compound-channel evaporator comprises an upper pressing plate and a lower pressing plate which are in close fit with each other. A compound channel network is formed between the upper pressing plate and the lower pressing plate through inflation. Flowing refrigerant which is used for absorbing heat for evaporation is arranged in the compound channel network. The inflation-type compound-channel evaporator for the solar direct-expansion heat pump water heater has the advantages of simple structure, attractive appearance, high practicability, low cost and the like, and can enable the solar direct-expansion heat pump water heater to adapt to different climate and weather conditions.